Studi Kasus: Pengaruh Cognitive Behavior Therapy (CBT) pada Klien dengan Diagnosa Gangguan Afektif Bipolar - Ginting, Anette Isabella (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
This study aims to explore how the cognitive behavioural therapy affected a client with bipolar affective disorder. Participant was a 25-years-old woman (SM) who is diagnosed with bipolar disorder specify current or most recent episode: manic, depressed (F31.6). Before beginning the therapy session, the participant completed a series of assessment, including interview (autoanamnesa and alloanamnesa), observation, graphic tests (BAUM, DAP, HTP Wartegg) and Sack’s Sentence Completion Test (SSCT) to evaluate the participant’s personality, and Standard Progressive Matrices (SPM) to assess cognitive ability. Therapy was conducted in 5 sessions (1 session each week) with additional daily task to track the thoughts and behaviors pattern. The result shows a decrease in depression scores (BDI-II) and also SUDS (Subjective Unit Disturbance Scale). Qualitatively, CBT helps the participant to select her own automatic negative thoughts and form more adaptive thinking pattern by her own. Participant also shows an increasing score in GAF (Global Assesment Functioning) after completing the whole therapy sessions